2017
DOI: 10.4103/0973-1296.204618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helix aspersa extract on TNFα, NF-κB and some tumor suppressor genes in breast cancer cell line Hs578T

Abstract: Background:The garden snail, Helix aspersa, is a big land snail widely found in the Mediterranean countries. It is one of the most consumed species and widely used in zootherapy.Objective:The present study was carried out to investigate for the first time the first time the antitumor activity of an aqueous extract from Helix aspersa.Materials and Methods:The effect of H. aspersa extract was studied on a triple negative breast cancer cell line Hs578T. Firstly, the morphological changes and the mode of cell deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Extracts from tissues of H. aspersa Müller were shown to possess anticancer activity against breast cancer cells (Hs578T) [ 5 ]. Two fractions of mucus of another snail, the giant African snail Achatina fulica , decreased viability of breast cancer cells (MCF-7) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extracts from tissues of H. aspersa Müller were shown to possess anticancer activity against breast cancer cells (Hs578T) [ 5 ]. Two fractions of mucus of another snail, the giant African snail Achatina fulica , decreased viability of breast cancer cells (MCF-7) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphatase and tensin homolog (PTEN) a tumor suppressor gene, has been reported to be involved in various types of cancer ( 15 , 16 ). Mutations in PTEN have been reported to be involved in the development of cancer ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The hemolymph of the land snail, Helix lucorum and the marine snail Rapanavenosa exhibited potential anticancer activities against human bladder carcinoma cells (T-24) (Dolashka et al, 2015). Furthermore, tissue extracts of some garden snails including Helix aspersa and Actinia equina were shown to possess anticancer activity against breast cancer cells leukemia-derived cells (Teerasak et al, 2016;El Ouar et al, 2017). Isolated hemocyanins from the terrestrial snail Helix pomatia and the marine snail Rapanathomasiana showed promising antiproliferative effects on colon carcinoma (Gesheva et al, 2014).…”
Section: Discussionmentioning
confidence: 99%